On a Certain Transport Scheduling Problem for Heterogeneous Bus Fleet - Peter Czimmermann (Communications - Scientific letters of the University of Zilina, 2006)
In this paper we consider a certain transport scheduling problem for heterogeneous bus fleet. We suppose that some restrictions are given for sets of vehicles and trips. We study some special cases of this problem that can be solved in polynomial time.